The implementation of canon law in Ontario regarding decent support for retired Diocesan clergy - Kiffman, Robert M (University of Ottawa (Canada), 2004)
More Roman Catholic clergy enter retirement every year. Vatican II and the Code of Canon Law, 1983, introduced language common to the marketplace and changed the framework of support for a presbyter. Changes included, such terminology as wages, remuneration and contract; the values, rights, and criteria to determine the support due to an active, inactive or a retired presbyter. The right to support, including housing, normally for life, resides in the juridical bond of incardination. The pertinent canons in the matter of support for clergy are canons 281 and 538, §3. Are the dioceses of Ontario in compliance with the laws pertinent to the support of a presbyter in retirement? Chapter One provides the biblical and historical foundations associated with the support of ministers of religion in the Old and New Testaments, early Christianity up to the Edict of Milan in 313, and in the 1917 Code . Chapter One considers problems associated with "wandering clergy" and the development of the notion of canonical title to ensure the support of the presbyter for life. The titles of benefice, patrimony, and pension existed in the context of property law. The ordinary title for ordination in Ontario, "service to the diocese" is a non-proprietary title included in the 1917 Code that shifted the source of rights to support from property law to law of contract for hire. Chapter Two considers the ecclesiastical documents from Vatican II and the 1983 Code concerning presbyteral support. Social justice and the dignity of the human person and the value of a presbyter's labour is the cause of rights to obtain support in commutative and distributive justice. Canonical issues revolve around the obligation of the Christian faithful to provide support, the sources and loss of support in active ministry, incapacity, and in retirement. Chapter Three considers the law and CCCB decree, No. 31, measured against a number of objective economic standards of time and place. The chapter considers constitutive elements of support, classifications of housing and the tax implications of low rent. According to the narrative accounts of two surveys, the "Priests' Survey on Retirement" indicates the current diocesan practice of providing support is flawed.
Keywords: Religion, Clergy.; Law.